G-quadruplex DNA inhibits unwinding activity but promotes liquid–liquid phase separation by the DEAD-box helicase Ded1p - Gao, Jun (Chem Commun (Camb), 2021)
G-quadruplex DNA interacts with the N-terminal intrinsically disordered domain of the DEAD-box helicase Ded1p, diminishing RNA unwinding activity but enhancing liquid–liquid phase separation of Ded1p in vitro and in cells. The data highlight multifaceted effects of quadruplex DNA on an enzyme with intrinsically disordered domains.